2022
DOI: 10.1111/odi.14127
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune disorders in oral lichen planus: A systematic review and meta‐analysis

Abstract: Objectives The association of OLP with other autoimmune processes points to the possibility that OLP‐affected patients are actually developing an autoimmune status that predisposes them to autoaggression against different targets. This systematic review and meta‐analysis aim to evaluate the current evidence on the prevalence of autoimmune disorders in patients with OLP and their magnitude of association. Methods We searched PubMed, Embase, Web of Science, Scopus databases for the studies published before May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 49 publications
0
38
2
Order By: Relevance
“…previous study [15]. A recent meta-analysis study indicated a significantly high prevalence of thyroid disease among the patients with OLP compared with controls [16]. The association between OLP and thyroid diseases appears to be due to their pathophysiological similarities, as both diseases are caused by an autoimmune mechanism involving cytotoxic T cells and are more prevalent in women.…”
Section: Oral Lichen Planus (Olp)mentioning
confidence: 83%
“…previous study [15]. A recent meta-analysis study indicated a significantly high prevalence of thyroid disease among the patients with OLP compared with controls [16]. The association between OLP and thyroid diseases appears to be due to their pathophysiological similarities, as both diseases are caused by an autoimmune mechanism involving cytotoxic T cells and are more prevalent in women.…”
Section: Oral Lichen Planus (Olp)mentioning
confidence: 83%
“…The current consideration of OLP as an autoimmune disease [ 8 , 10 ] has raised the hypothesis that its malignant transformation could be mediated by the inflammatory infiltrate that systematically appears, in a similar way to what occurs with other autoimmune diseases such as ulcerative colitis or primary biliary cirrhosis. There has been some primary level studies published -retrospective cohorts- on the expression and possible participation of some oncoproteins and tumor-suppressor proteins in the OLP malignization process, together with other papers evaluating cell proliferative activity, as well as the development of apoptosis in OLP epithelial cells [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 92 , 93 , 94 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms involved in the malignant transformation of OLP are largely unknown, although they seem to be related, as in other autoimmune diseases, to the oncogenic effects linked to the chronic inflammatory aggression established in this lesion [ 8 , 10 ]. Our group has developed in recent years a line of research that has resulted in the publication of several primary-level studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the rationale for the introduction of this term (LDR) is weak and the available data suggest that these LDRs could correspond to cases of OLP in older people who, for multiple and frequent reasons at this age, need to take diverse drugs. This idea is also supported by the frequent use of drugs in patients with OLP due to their frequent association with other systemic diseases, including diabetes, hypertension, thyroid disease and other autoimmune processes that will require the use of drugs, many of which have been implicated in the development of LDR (De Porras‐Carrique, González‐Moles, et al, 2022; De Porras‐Carrique, Ramos‐García, et al, 2022). The identification of a drug as an unequivocal causative agent requires a positive result from the application of the C‐D‐R protocol, which requires the patient to recognise a close temporal relationship between the drug and the onset of the lesions.…”
Section: Oral Lichenoid Reactionsmentioning
confidence: 99%